DEVELOPMENT OF METHODOLOGY FOR THE CALCULATION OF THE PROJECT INNOVATION INDICATOR AND ITS CRITERIA COMPONENTS - Mariya Vishnevskaya; Dmytro Kozenkov; Olha Kaut (Baltic Journal of Economic Studies, 2017)
Two main components of the problem studied in the article are revealed. At the practical level, the provision of the convenient tools allowing a comprehensive evaluation the proposed innovative project in terms of its possibilities for inclusion in the portfolio or development program, and on the level of science – the need for improvement and complementing the existing methodology of assessment of innovative projects attractiveness in the context of their properties and a specific set of components. The research is scientifically applied since the problem solution involves the science-based development of a set of techniques, allowing the practical use of knowledge gained from large information arrays at the initialization stage. The purpose of the study is the formation of an integrated indicator of the project innovation, with a substantive justification of the calculation method, as a tool for the evaluation and selection of projects to be included in the portfolio of projects and programs. The theoretical and methodological basis of the research is the conceptual provisions and scientific developments of experts on project management issues, published in monographs, periodicals, materials of scientific and practical conferences on the topic of research. The tasks were solved using the general scientific and special methods, mathematical modelling methods based on the system approach. Results. A balanced system of parametric single indicators of innovation is presented – the risks, personnel, quality, innovation, resources, and performers, which allows getting a comprehensive idea of any project already in the initial stages. The choice of a risk tolerance as a key criterion of the “risks” element and the reference characteristics is substantiated, in relation to which it can be argued that the potential project holds promise. A tool for calculating the risk tolerance based on the use of matrices and vector analysis is proposed. Based on the fuzzy sets theory, a calculation of the “personnel” component is suggested on the basis of the analysis of the conformity factor of execution of potential project operations to the required competencies of the project manager. The suggested technology assessment as a part of a comprehensive indicator of the project innovation, unlike other technologies, considers the compliance of the project product characteristics with the consumers’ requirements and the options of a specific project. On the basis of ideal and matrix modelling, a mathematical model is obtained for determining the prospects of realizing consumer’s expectations regarding the project product. Practical implications. As a result of applying the suggested indicator of innovation, it is possible to obtain the information on the degree of the project innovativeness and risk tolerance, if the available resources are sufficient, whether the set of competencies of a project manager is in compliance with the project works, and whether the project product meets the requirements of the consumers. It is found that the innovation of projects can be considered as necessary and sufficient information for making optimal decisions. Simplicity, ease of use, efficiency, measurability, adaptability of innovation indicator extend its effectiveness in the field of the project management and provide the organization with a new tool for making appropriate management decisions. Application of the integrated project innovation indicator complements the classical methods of analysis of options, increases the effectiveness of the application of project management tools, especially at the stage of project selection to portfolio or program. The results of the research can be used for further development of scientific and methodological foundations to form a balanced system of indicators of innovative projects. The results implementation is a methodological and organizational basis for creating effective systems and technologies for managing the project programs and portfolios.